Coastal Flood Inundation Mapping and Hazard Zonation of Bandar Lampung City Using GIS and OpenStreetMap - Agung Mahadi Putra Perdana; Meida Cahyo Untoro; Ilyas Ilyas; Mugi Prasetiawan; Amir Faisal (Media Komunikasi Geografi, 2026)
The coastal area of Bandar Lampung City is increasingly exposed to flood inundation from extreme rainfall and tidal flooding associated with sea-level rise, requiring an integrated spatial mapping approach. This study maps coastal flood inundation using Sentinel-1 SAR imagery, develops flood hazard zonation through the Analytical Hierarchy Process (AHP), and disseminates the results through an OpenStreetMap-based WebGIS platform. The methodology combines Random Forest classification of Sentinel-1 dual-polarization imagery (VV/VH) using fourteen feature variables, AHP–Weighted Linear Combination for hazard zonation based on seven physical parameters (CR = 0.047), LSTM-based prediction, and Smart GIS Dashboard development using PostGIS, GeoServer, Leaflet, and MapLibre. The results indicate 1,247 ha of inundated area, representing 13.9% of the 8,956 ha study area, mainly concentrated in Teluk Betung Selatan and Panjang. Hazard zonation identifies 847 ha as high hazard, 1,932 ha as medium hazard, and 6,177 ha as low hazard. High-hazard zones expose 4,312 buildings, 27.3 km of roads, and 23 critical facilities. The Random Forest model achieved 93.7% accuracy, while the WebGIS platform obtained a SUS score of 74.6. Unlike previous isolated mapping approaches, this study integrates machine learning, multi-criteria hazard assessment, asset exposure analysis, and open-source WebGIS dissemination to support coastal mitigation and spatial planning.